The languages of politics. Volume 2 - Degani, Marta; Frassi, Paolo; Lorenzetti, Maria Ivana (Newcastle upon Tyne, England : Cambridge Scholars Publishing, 2016)
The Languages of Politics/La politique et ses langages provides a multifaceted view of major approaches to the study of political discourse from an interdisciplinary perspective. To date, most contributions to the analysis of political discourse have come from the fields of rhetoric, (critical) discourse analysis, cognitive linguistics, pragmatics, lexicology, lexicography, and, more recently, multimodal discourse analysis. The papers in this volume build their investigations on these perspectives, and provide new and diversified insights into this vast area of research. Besides considering multiple approaches, the book also adds to the current debate on the languages of politics by combining a range of theoretical and methodological considerations, and by featuring contributions in both English and French.
Intro -- Contents -- Acknowledgments -- Introduction -- Section I: Political Discourse and Political Genres -- Chapter One -- Chapter Two -- Chapter Three -- Chapter Four -- Chapter Five -- Section II: The Lexicology and Lexicography of Politics -- Chapter Six -- Chapter Seven -- Chapter Eight -- Chapter Nine -- Section III: Historical Perspectives on Political Discourse -- Chapter Ten -- Chapter Eleven -- Section IV: Political Language in the New Media -- Chapter Twelve -- Chapter Thirteen.
Includes bibliographical references at the end of each chapters.
Description based on online resource; title from PDF title page (ebrary, viewed January 4, 2017).
Keywords: Discourse analysis -- Political aspects